SCIENCE TEACHER ABILITY TO DESIGN STUDENT SPIRITUAL ATTITUDE INSTRUMENTS - Ida Meutiawati; Fitriyawany Fitriyawany; Sabaruddin Sabaruddin (Universitas Islam Negeri Ar-Raniry, 2024)
Each teacher must be able to harmonize the assessment of cognitive and psychomotor aspects with the assessment of students' affective aspects in learning. Most of the research conducted in Aceh is still limited to the development of spiritual attitude assessment instruments, while studies describing the ability of science teachers to design spiritual attitude assessment instruments are still very limited. This study aims to determine the ability of junior high school science teachers in the Pidie District to prepare questions to measure students' spiritual attitudes. The research uses the Mix method, with documentation and interview analysis techniques using the Miles and Huberman models, and the feasibility validity of the spiritual attitude assessment instrument uses a Likert scale and is then presented using percentage calculations. A purposive sampling technique is applied in determining the sample. The results showed that most of the teachers had less ability to design spiritual attitude assessment instruments. Few teachers could compile a comprehensive spiritual attitude assessment instrument per the attitude assessment technique in the 2013 curriculum. The first obstacle science teachers faced was formulating assessment indicators, where some teachers did not understand spiritual attitudes with social attitudes in learning. Secondly, assessment techniques with Rubik's or scoring guidelines were not in line with the demands of the 2013 curriculum.